Reformation of Storied Assumptions of Parents and Poverty - Pushor, Debbie; Ciuffetelli Parker, Darlene (International Journal about Parents in Education, 2023)
We begin this article by introducing research into a curriculum of parents (Pushor, 2011, 2013). We then make visible how pre-service teachers’ engagement in such a curriculum creates possibilities for teachers to actively resist deficit-based conceptualizations and to deepen their understanding of discourses of poverty and of representations of parents. The research is situated in Dewey’s (1938) foundational conception of experience as education and in Clandinin and Connelly’s (2000) explication of a narrative inquiry framework comprised of stories of experience. We take up Ciuffetelli Parker’s (2013) notions – narrative reveal, narrative revelation, and narrative reformation – which we use to examine stories which illuminate one pre-service teacher’s growing understanding of the complexities of teaching in a school community affected by poverty. Using Ciuffetelli Parker’s narrative elements, we demonstrate how a teacher candidate, who experienced an explicit curriculum of parents, came to see parents affected by poverty as knowing and knowledgeable and as having an important place and voice in their children’s schooling and education